Evaluation of Sodium and Potassium Contents In Portuguese Diet - Nascimento, Ana (2021)
Sodium and Potassium are essential micronutrients, considered as nutrients of public health concern. Salt consumption in Portugal almost doubles WHO recommended maximum level of intake, contributing to a significant prevalence of non-communicable diseases. Moreover, excessive Na intake leads to an increase in blood pressure, whereas K intake leads to a balance between the two ions, which contributes to the regulation of blood pressure. Thus, WHO recommends not only restrictions on Na intake but also an adequate intake of K, which corresponds to a Na/K ratio bellow 1. The aims of this work were to assess Na and K general dietary intake and evaluate Na/K ratio for food groups under study. Samples were selected according to Total Diet Study (TDS), based on foods as consumed, in Portuguese diet. Analyzed samples (n=150), constituting 11 food groups, were grouped according to food classification system FoodEx2 level 1. Sodium and potassium levels were determined using Inductively Couple Plasma Atomic Emission Spectrometry - ICP-OES. Sodium and potassium contents ranged from <LOQ (8.0)-2108 mg/100 g in several fruits, vegetables, ham and bacon and <LOQ (10.0)-1583 mg/100 g in lupins, meat broths and in fresh cod. Molar ratio Na/K presented, in general, lower levels in raw products (as fruits, legumes and vegetables), and higher levels in processed foods, generally contributing to markedly high levels of Na. Despite the strategy for reducing salt, the encouragement of healthier cooking, together with the lowering of dietary sodium-potassium ratio by increasing consumption of unprocessed or minimal processed foods, that are naturally low in sodium and, also rich in potassium, can be a good strategy on health promotion and disease prevention. In that matter, Portuguese TDS studies can be an important resource to assess dietary intake of Na and K by the population and a complement in the definition of nutrition policies.